2017
DOI: 10.1097/igc.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncological Outcome After Conventional Radical Hysterectomy Versus 2 Nerve-Sparing Modalities for Early Stage Cervical Cancer

Abstract: The nerve-sparing radical hysterectomy shows a similar oncological outcome compared with the CRH. The more radical Swift version of nerve-sparing techniques is preferable to the former LNSRH procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, in the recent years minimally invasive surgery has emerged for the treatment of several benign and malignant conditions, including CC [10111213]. Accumulating data from well conducted retrospective and prospective study underlined that minimally invasive surgery upholds long-term outcomes of open abdominal procedures, minimizing postoperative morbidity [1415161718], but mature data on long-term safety of minimally invasive radical hysterectomy are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the recent years minimally invasive surgery has emerged for the treatment of several benign and malignant conditions, including CC [10111213]. Accumulating data from well conducted retrospective and prospective study underlined that minimally invasive surgery upholds long-term outcomes of open abdominal procedures, minimizing postoperative morbidity [1415161718], but mature data on long-term safety of minimally invasive radical hysterectomy are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…van Gent et al reported similar survival outcomes between nerve-sparing RH and conventional RH. 22 Q-M type C1 RH is a highly precise surgery that lack popularity in China. Additionally, full evaluation data related to postoperative bladder, anorectal, and sexual dysfunction is not available in the Four C database.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Querleu-Morrow classification8,9 provides a reproducible anatomic terminology for NSRH, it was not designed to impose a universal surgical technique. The description of surgical procedures and energy instruments for NSRH and TRH differ considerably among different studies,17,18 suggesting that different surgeons are performing operations without standardized techniques and processes, even though the autonomic nerves form well-defined anatomic boundaries for NSRH. The success determining factors of nerve-sparing, such as FIGO stage or pathologic subtype, were little known 5,19,20.…”
Section: Discussionmentioning
confidence: 99%